Managing Alternative Patient Appointments Using P-Graph Methodology. - SÜLE, Zoltán; BAUMGARTNER, János; VATHY-FOGARASSY, Ágnes (Studies in Health Technology & Informatics, 2020)
Background: Patient appointment scheduling is one of the main challenging tasks in the healthcare administration and is constantly in the focus of theoretical researches. Objectives: The aim of this study was to investigate the applicability of the P-graph (Process graph) methodology to find the n-best alternative for patient's scheduling. Methods: The patient appointment scheduling task was formalised as an integer linear programming problem and was considered as a process network synthesis problem. The optimal and n-best alternative solutions were determined by an efficient branch and bound algorithm implemented in a decision support system. Results: Experimental results show, that the P-graph methodology can be effectively applied to produce the optimal scheduling for the examinations and to find the alternatives of the best scheduling.